Robust relation between public procurement for innovation and economic development - Bento, N.; Sousa, C.; Trindade, P.; Mamede, R. P.; Fontes, M.; Alves, T. (Economics Letters, 2022)
We found a solid and robust relationship between the share of public procurement for innovation (PPI) in public procurement and GDP per capita for 30 European countries. The share of PPI is highly associated with determinants from “demand pull” as well as “supply push”. These findings open new opportunities for the study of the drivers of public procurement for innovation. The study also provides a new methodology for benchmarking.